DETECTION OF LOW CONCENTRATIONS OF FINE-GRAINED IRON OXIDES BY VOLTAMMETRY OF MICROPARTICLES - van Oorschot I.H.M.; Grygar T.; Dekkers M.J. (My University, 2001)
Mineralogical discrimination of iron oxides in soils and sediments is not a trivial task, mainly because of their small grain size and low concentration. With mineral-magnetic techniques, highly magnetic ferrimagnetic spinels can be determined with a very low detection limit (~10 ppm). Unfortunately, the magnetic signal of natural samples is often dominated by magnetite, and in particular the expression of weakly magnetic antiferromagnetic minerals is suppressed by this high signal. In contrast, electrochemical techniques, such as voltammetry of microparticles (VMP) are not affected by these differences in magnetic signal. VMP makes use of the electrochemical law that iron(oxy)(hydr)oxides can be reductively dissolved at potentials that are specific for their mineralogy and reactivity. Therefore, by scanning over a potential range and monitoring the potential at which a reaction occurs, one can specify the type of minerals present. VMP can be applied to samples without requiring any form of pre-treatment. The method is rapid, comparatively straightforward to interpret, and requires little amount of sample (μg). However, the detection limit of VMP on natural samples has not yet been investigated. Here, we present a pilot study of the use of VMP in the identification of the ferric oxides of natural samples from Spanish red beds of Miocene age. A standard addition method with pyrolusite as internal standard enabled semi-quantitative analysis of the samples; concentrations of (anti)ferromagnetic iron(oxy)(hydr)oxides down to ~0.1 wt% could be detected.
Keywords: ELECTROCHEMICAL PROPERTIES; SOIL SURVEYS; MAGNETITE; HEMATITE; GOETHITE; MAGNETIC MINERALS; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен